2020
DOI: 10.1371/journal.pone.0244283
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in the incidence of peritoneal dialysis-related peritonitis disclose an increasing relevance of streptococcal infections: A longitudinal study

Abstract: Background The selective impact of strategies for prevention of PD-related peritonitis (PDrP) may have modified, in the long term, the causal spectrum, clinical presentation and outcomes of these infections. Objectives To compare trends in the incidence of PDrP by different microorganisms during a 30-year period, with a particular focus on streptococcal infections. To analyze the clinical presentation and outcomes of these infections. Secondarily, to investigate how the isolation of different species of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…An increasing trend of streptococcal peritonitis has been observed in longitudinal studies, 321,322 mostly secondary to viridans groups (including oralis , sanguis and gordonii ). For viridans group streptococci , there is emerging evidence of mixed or polymicrobial strains with lower susceptibility to ampicillin, penicillin and ceftriaxone being encountered.…”
Section: Subsequent Management Of Peritonitismentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing trend of streptococcal peritonitis has been observed in longitudinal studies, 321,322 mostly secondary to viridans groups (including oralis , sanguis and gordonii ). For viridans group streptococci , there is emerging evidence of mixed or polymicrobial strains with lower susceptibility to ampicillin, penicillin and ceftriaxone being encountered.…”
Section: Subsequent Management Of Peritonitismentioning
confidence: 99%
“…The reported cure rate of streptococcal peritonitis exceeds 85%, and most patients can continue PD. 320,321…”
Section: Subsequent Management Of Peritonitismentioning
confidence: 99%
“…The sources of these variations may be center-related factors, such as center size, topical antibiotic prophylaxis, and PD training [2]. To date, few articles describe the chronological changes in peritonitis rates, and most reports are from a single center [12,[14][15][16][17]. In our multicenter study, we demonstrated a significant decrease in the peritonitis rate during the study period, especially over the last 3 years, which could be attributable to the significant decrease in G+ PDAP, G-PDAP, and culture-negative PDAP rates.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 , 35 Similar trends in the reduction of peritonitis rates have been observed worldwide. 4 , 36 , 37 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%